Virtual Directed Radicalization: Digital Bai'at and "DIY" Terrorism Among Adolescents - Muhamad Syauqillah; Ami Prindani; Juwarti Hafsah; Achmad Sauri (Bulletin of Community Engagement, 2026)
This study examines the cyber radicalization process among Indonesian adolescents, analyzing their transition from digital exposure to operational readiness for terrorism. Utilizing a qualitative case study approach, data were collected through in-depth interviews and document analysis of three adolescents exposed to radical ideologies. The findings were interpreted through the Three Stages of Terrorism Framework. Results reveal a structured progression: the pre-radicalism phase is driven by psychosocial vulnerabilities and identity crises; the exposure phase is accelerated by social media algorithms, filter bubbles, and echo chambers; and the terror act phase manifests in operational capabilities, including online pledges of allegiance (bai'at) and "Do-It-Yourself" (DIY) bomb-making. Furthermore, the study introduces the concept of Virtually Directed Radicalization (VDR), illustrating how anonymous online facilitators remotely guide vulnerable youth from passive content consumption to binding operational commitments. The study concludes that cyberspace now functions not merely as a propaganda medium, but as a comprehensive ecosystem for ideological indoctrination and clandestine operational preparation, necessitating urgent, digitally informed counterterrorism and psychosocial interventions.